Fabrication and characterization of low cost cobalt oxide-based catalyst beads - Ng, Qin Hui. (2013)
As the world is facing shortage of energy resources, fuel cell is one of the potential clean energy techniques that can be used widely in the future. Therefore, source of hydrogen is getting more and more attention nowadays. Hydrogen can be produce with various method such as hydrolysis of metal borohydride, water electrolysis, steam reforming, thermochemical cycles that can be used for water splitting etc. For example, hydrogen can be produce by hydrolysis sodium borohydrides stabilized by NaOH. Such hydrolysis reaction can be accelerated by noble/transition metal. Cobalt based catalysts had been proved that it is efficient and relatively low cost compared to noble metals. In this project, the phase transformations of cobalt oxide were determined by X-ray diffraction using Cu Kα radiation at room temperature. The effect of the pore former, graphite on the porosity and mechanical strength of the beads was determined using the Archimedes Principle and Instron 5565 Universal Material Testing Machine, respectively. The morphology of cobalt oxide-based beads before and after catalytic reaction was studied by Field Emission Scanning Electron Machine. Besides that, hydrogen release accumulated volume from sodium borohydride solution with catalyst beads removed had been investigated. It had been found that the activation energy of the catalytic reaction of the beads with various cobalt and graphite content at different sintering temperature were in the range of 43 – 66 kJ mol-1. The hydrogen generation rate increased as the sintering temperature increased until it reached 1200oC. The maximum compressive load of the beads was enhanced by the sintering temperature. The beads can be hydrolysis completely in 80 min.